2021
DOI: 10.1097/cm9.0000000000001628
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in leukemia and antioxidant treatment

Abstract: Oxidative stress is caused by the imbalance between the generation of free radicals/reactive oxygen species (ROS) and the antioxidant defense systems, which can activate various transcription factors and affect their transcriptional pathways. Oxidative stress plays an important role in the occurrence and development of leukemia and is closely related to the treatment and prognosis of leukemia. The standard chemotherapy strategies for the pre-treatment of leukemia have many drawbacks. Hence, the usage of antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Hypoxia is common in many chronic tumor diseases. [ 13 ] Recent studies revealed that physiological hypoxia in BM promotes communication deficiency between hematopoietic stem cells (HSCs) and BMSCs in some hematological malignancies. [ 14 ] HIF-1α is a key transcription factor associated with hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia is common in many chronic tumor diseases. [ 13 ] Recent studies revealed that physiological hypoxia in BM promotes communication deficiency between hematopoietic stem cells (HSCs) and BMSCs in some hematological malignancies. [ 14 ] HIF-1α is a key transcription factor associated with hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to single trace elements, the positive value of SCZR was meaningful, and the ratio suggests that patients were in a condition of oxidative stress [27]. While oxidative stress plays an important role in the occurrence and development of leukaemia and is closely related to the treatment and prognosis of leukaemia [38]. Meanwhile, the SCZR was an indicator of the nutritional status of Zn [39].…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance between the production of reactive oxygen species (ROS) and antioxidant defense mechanisms, which can activate different transcription factors and alter their transcriptional pathways, results in oxidative stress. Leukemia's occurrence and progression, as well as its treatment and prognosis, are all directly impacted by oxidative stress (Dong et al, 2021).…”
Section: Oxidative Stressmentioning
confidence: 99%